2018
DOI: 10.1111/jace.15874
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐insensitive piezoelectricity in lead‐free NaNbO3‐based ceramics

Abstract: In this work, we report a lead‐free piezoelectric ceramic of (0.9‐x)NaNbO3‐0.1BaTiO3‐xBaZrO3, and the effects of BaZrO3 on the phase structure, microstructure, electrical properties and temperature stability are investigated. A morphotropic phase boundary‐like region consisting of rhombohedral (R) and tetragonal (T) phases is constructed in the compositions with x = 0.035‐0.04. More importantly, in situ temperature independence of the piezoelectric effect {piezoelectric constant (d33) and strain} can be achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Although ultrahigh piezoelectricity was reported in barium titanate (BT)-based ceramics, [38] their low Curie temperatures (T C < 120 °C) lead to complete depolarization of the ceramics with temperature approaching 100 °C. Similar phenomenon was also reported in sodium niobate (NN)-based ceramics due to the relatively low T C. [39] Figure 3e further summarizes the piezoelectric variation [Δd 33 = |(d 33T /d 33RT ) − 1| *100%] of some representative KNN-based ceramics in the temperature range of 25-100 °C. It can be observed that there is always a large d 33 variation reported in traditionally designed KNN-based cer amics, [16,17,19,21,23,24] while the studied composite KNN-based ceramics exhibit an average room temperature d 33 value of ≈330 pC N −1 with variation below 6% up to 100 °C.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Although ultrahigh piezoelectricity was reported in barium titanate (BT)-based ceramics, [38] their low Curie temperatures (T C < 120 °C) lead to complete depolarization of the ceramics with temperature approaching 100 °C. Similar phenomenon was also reported in sodium niobate (NN)-based ceramics due to the relatively low T C. [39] Figure 3e further summarizes the piezoelectric variation [Δd 33 = |(d 33T /d 33RT ) − 1| *100%] of some representative KNN-based ceramics in the temperature range of 25-100 °C. It can be observed that there is always a large d 33 variation reported in traditionally designed KNN-based cer amics, [16,17,19,21,23,24] while the studied composite KNN-based ceramics exhibit an average room temperature d 33 value of ≈330 pC N −1 with variation below 6% up to 100 °C.…”
Section: Resultssupporting
confidence: 77%
“…The new concept of the phase transition gradient can effectively solve the temperature instability of d 33 inherently associated with PPB, which is not achievable in conventional strategies including texture technique, [5,21,37] fine composition tuning, [26] and diffused phase transition. [22] The in situ d 33 -T of the structural gradient multilayer composite is compared to the actively studied lead-free ceramic systems (Figure 3d), [17,38,39] demonstrating a superior piezoelectric temperature stability in the temperature range of 25-100 °C. Although ultrahigh piezoelectricity was reported in barium titanate (BT)-based ceramics, [38] their low Curie temperatures (T C < 120 °C) lead to complete depolarization of the ceramics with temperature approaching 100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the lead-free dielectric capacitors have inspired more and more research interest around the world . Among the reported lead-free materials, NaNbO 3 -based solid solutions are a notable environmentally friendly counterpart with excellent piezoelectric, electrostrictive, and electrocaloric properties, as well as energy storage properties. Pure NaNbO 3 ceramics are antiferroelectric P phase at ambient temperature but generally exhibit square P–E curves because of the appearance of the electric-field-induced metastable ferroelectric Q phase, ,, leading to a large P r and thus an unsatisfied energy storage property. However, the NaNbO 3 -based ceramics with antiferroelectric P phase still exhibit relatively low W rec (<2 J/cm 3 ) as a result of the low driving electric field for antiferroelectric–ferroelectric phase transition.…”
Section: Introductionmentioning
confidence: 99%